Aggregation induced enhanced and exclusively highly Stokes shifted emission from an excited state intramolecular proton transfer exhibiting molecule12. (12th December 2016) - Behera, Santosh Kumar; Murkherjee, Anwesha; Sadhuragiri, G.; Elumalai, Palani; Sathiyendiran, M.; Kumar, Manishekhar; Mandal, Biman B.; Krishnamoorthy, G.
Abstract : The inner filter effect due to self-quenching dominates the normal emission of dyes at higher concentrations, which would limit their applications. Since normal emission was also observed with aggregation induced emission enhancement (AIEE) active excited state intramolecular proton transfer (ESIPT) exhibiting molecules, two new molecules are synthesized and studied to obtain normal emission free AIEE. The molecules are 4-(3-(benzo[ d ]thiazol-2-yl)-5- tert -butyl-4-hydroxybenzyl)-2-(benzo[ d ]thiazol-2-yl)-6- tert -butyl phenol (bis-HPBT) and its oxazole analogue (bis-HPBO). Of these molecules, bis-HPBT, which is weakly fluorescent in tetrahydrofuran solution, shows a sudden high enhancement in fluorescence upon addition of 70% water due to the formation of aggregates. Though the normal emission is also observed in tetrahydrofuran, it is completely eliminated in the aggregates, and the aggregates display exclusive tautomer emission. However, bis-HPBO does not emit such an exclusive tautomer emission in the water/tetrahydrofuran mixture. The enhancement in the fluorescence quantum yield of bis-HPBT in 70% water is ∼300 times higher than that in tetrahydrofuran. The modulated molecular structure of bis-HPBT is the cause of this outstanding AIEE. The observation of almost exclusive tautomer emission is a new additional advantage of AIEE from bis-HPBT over other ESIPT molecules. Since the tautomer emission is highly Stokes shifted, no overlap with the absorption spectrum occurs and therefore, the inner filter effect is averted. The aggregated structure acts as a good fluorescence chemosensor for metal ions as well as anions. The aggregated structure is cell permeable and can be used for cell imaging.